The Development of Instructional Using Case-Based Learning Through Collaborative Learning to Promote Pre-Service Teachers’ Ability to Learning Management - Sithsungnoen, Chanasith (Humanities, Arts and Social Sciences Studies, 2020)
The objectives of this study were to 1) develop an instruction using Case-Based Learning (CBL) and Collaborative Learning (CL) to promote the instructional design abilities of Pre-Service Teachers; 2) study the effectiveness of the instructions using conducted model by looking at: 2.1) comparison the learning outcomes of the Pre-Service teachers before and after studying, 2.2) study the learning outcomes of the Pre-Service Teachers’ instruction, 2.3) study the instructional design ability of the Pre-Service teachers and 2.4) feedback of Pre-Service teachers towards the model. The samples were 25 undergraduate Pre-Service teachers at the Faculty of Education, Silpakorn University in Thailand. The samples were purposively selected. The instruments included: 1) instruction using CBL and CL, 2) a comprehensive test; 3) assessment on instructional design abilities; 4) assessment for delivering instructions, and 5) survey on students’ feedback. The study utilized statistics for comparisons including mean, standard deviation, and T-score. The results were as follows: 1) The instruction using CBL and CL for promoting the instructional design abilities of Pre-Service Teachers applies to a 6-step approach called DAISI. The steps are: First: define a situation or event. Second: analyze the problems of the situation. Third: identify alternative solutions. Fourth: search results. Fifth: share knowledge. Sixth: implement the results. 2) The effectiveness of conducted model The Post-Research Stage were: 2.1) The learning outcomes of Pre-Service Teachers after using model were significantly 0.5 higher than before their attendance. 2.2) The overall learning outcomes of Pre-Service Teachers were in a “good” level (x̄ = 23.92, SD = 1.89). The Pre-Service Teachers’ ability to design instructions using model were in a “very good” level (x̄ = 86.66). 2.3) The Pre-Service Teachers’ ability to deliver instructions (field experience) using model was in “good” level (score 76/100). 2.4) Pre-Service Teachers’ satisfaction towards the model was high (x̄ = 4.28, SD = 0.71).